Vegetation with pronghorn - Milchunas, Daniel, photographer (Colorado State University. Libraries, 2007)
Broad view of vegetation across SGS with fencing and pronghorn in center.
Keywords: grazing; SGS; shrublands; landscapes; animals; pronghorn